Colonic cytokines for severe ulcerative colitis - Ye. A. Konovich; K. Ye. Shirokikh; I. L. Khalif; M. V. Shapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To assess colonic cytokines profile at severe ulcerative colitis (UC). Material and methods. Overall 48 biopsy specimens of colonic mucosa obtained at resection operations in 7 patients with total form of UC were investigated. All patients underwent total colectomy for severe treatment-resistant UC. Activity of inflammatory process was determined by severity of erosive and ulcerative lesions of the colon. Cytokine concentration was evaluated in supernatant fluid after centrifugal separation of 10 mg biopsy specimen homogenate by the protein analyzer «Bio-Plex» («Bio-Rad», USA). Colonic mucosa biopsy specimens of unaffected parts of the large intestine resected in 10 patients with colorectal cancer were used as controls. Results. Tissue levels of IL-1β, IL-8, IL-6, TNF-α (tumor necrosis factor-α), IFN-γ (interferon-γ), IL-17 and IL-12 in biopsy specimens the large intestine of UC patients were significantly elevated. The most significant elevation was found for IL-8 and IL-1β, with the ratio of 3:1 (in the control group 0,35:1). The cytokine content in biopsy specimens of the large intestine has been increased in comparison to terminal portion of the small intestine, and the cytokine level in the left and transverse part of the colon was higher, than in cecum and ascending colon. At severe inflammation as compared to moderate inflammation the most significant increase was found for IL-8, IL-6 and TNF-α. Cytokine profile with the prevalence of IL-1β (IL-1β>IL-8>IL-6 (IFN-γ)>TNF-α) was observed in 14 (77,7%) of 18 biopsy specimens with moderate inflammation while similar cytokine pattern was observed in 9 (47,3%) of 19 biopsy specimens with severe inflammation (p=0,05). Domination of IL-8 (IL-8> IL-1β> IL-6 (TNF-α)> TNF-α (IL-6)) in cytokine profile was found in 3 of 18 (16,6%) biopsy specimens with moderate and in 9 of 19 (47,3%) biopsy specimens with a severe inflammation (p